Photodetector based ZnONPs/BiFeO3Ferroelectric Perovskite Heterojunction - Upadhyay R.K.; Jit S. (My University, 2025)
In this article, we report the semiconductor Zinc oxide and Bismuth oxide ZnO/BiFeO3 based photodetector device fabricated on ITO transparent glass substrate. The perovskite BiFeO3 is prepared using the solid-state method while ZnO prepared using a sol-gel method. The synthesized semiconductor oxide (ZnO) nanoparticles and ferroelectric perovskite BiFeO3 nanoparticles thin film characterized using BT-XRD, SEM, and UV-visible (UV) spectroscopy. XRD results of ZnO nanoparticles and perovskite BiFeO3 nanoparticles thin films confirm the hexagonal phase and rhombohedral phase of ZnO and perovskite BiFeO3 respectively. Scanning electron microscope images of ZnO and perovskite BiFeO3 show uniform distribution of nanoparticles. Finally, the ZnO/BiFeO3 based heterojunction based photodetector device is investigated for optoelectronics properties. © 2021 IEEE.